Strategi Komunikasi, Inovasi, dan Mitigasi Penyelenggaraan Ibadah Haji dan Umrah di Masa Pandemi - Ardiyamsi Sarmoko Saridi; Yoga Setyo Wibowo; Era Anggela (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
In the Covid-19 pandemic era, all national to international aspects has been affected, including religious activities such as the implementation of Hajj and Umrah. Saudi Arabia through The Ministry of Hajj and Umrah only allows domestic pilgrims in 2020. This has caused the Indonesian Government to cancel Hajj departures, thus prolonging the queue of pilgrims in Indonesia. The Indonesian Ministry of Religion needs to adjust the Hajj and Umrah policies in the pandemic era, by designing a message communication strategy, innovation and Hajj mitigation for prospective pilgrims. Problems and challenges in communicating the message, including differences knowledge of prospective pilgrims regarding Hajj procedures, the dominance of elderly prospective pilgrims, education levels, and various demographic characteristics of socio-economic need to be considered. This article aims to describe the expectations of prospective pilgrims for the 2021 hajj departure and how the right model of communication, innovation and mitigation strategy for hajj and umrah during the pandemic. This research method uses a mix-method approach through a survey involving 1201 prospective pilgrims from 34 provinces in Indonesia using telesurvey methods and literature studies. This research found that prospective pilgrims have high expectations (9.17 from 10) for the 2021 Hajj departure. In communicating information related to the implementation of the hajj and umrah pilgrimages during the pandemic, the government needs to produce clear, meaningful, one narrative, empathetic, consistent and contextual message. In addition, it also build harmonization of communication through the family system between government institutions, as well as providing guidance related to health protocols and emotional support by hajj officers and scholars to prospective pilgrims who get cancelation on hajj departure.